GENDERNESS OF AUTHORITIES OF CREATIVE POTENTIAL OSTOBISTOSTI - Kryzhanovska, Zoreslava Yuriivna (Psychological Prospects Journal, 2013)
In the statistics, creative people can be creative. Vznacheno, just creative - one of the necessary minds is becoming psychologically harmonious people. On the basis of empirical marriages, it is brought, just as creative reserves and special abilities are held for gender.